STEEL BOX GIRDER BRIDGE COMPONENT TRACEABILITY SYSTEM USING TREE STRUCTURE DIAGRAM AT PT BUKAKA TEKNIK UTAMA - Condro Wibawa; Metty Mustikasari; Dessy Tri Anggraeni (Jurnal Teknik Informatika (Jutif), 2023)
The International Organization for Standardization (ISO) through ISO 9001:2015requires every product to have product traceability. In response to these challenges, PT Bukaka Teknik Utama developes the Traceability System in the Steel Box Girder Bridge products. Traceability System built by adopting Tree Structure Diagram Concept to describe production system process currently runs. The production process start from identify raw material, cutting process, sub-assembly process, and assembly process. This concept is then translated into Relational Database by applying Parent-Child Concept. The result of this Traceability System is the system able to issue a list of product traceability including raw material information, sub-contractor/employee who work on them, etc, quickly and accurately. System testing was carried out using the black box method, where of the 37 items tested all functioned properly. Tests were also carried out to determine the accuracy and speed of the system compared to the manual method. Of the 10 tests carried out, the system traceability is exactly the same as the manual method with an average processing time of 3 seconds, compared to the manual method, which is 97.6 seconds.